PERANAN MARKETING MIX TERHADAP KEPUTUSAN PASIEN BEROBAT PADA RUMAH SAKIT UMUM DAERAH ROKAN HULU - Hasibuan, Mariani (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
General Hospital of Rokan Hulu is government owned hospitals Rokan Hulu which has been in operation for ± 9 years, As is known, the number of visits for patients in hospitals Rokan Hulu has increased from year to year. However, when compared with the total population that is in Rokan Hulu increasing each year is still far from the expected. Where the number of visits increased still fluctuating. Based on this fact raised the question of how to study the role of the Marketing Mix Decision Against Patients Treated At Hospital District General Rokan Hulu. The purpose of the study is to examine how the role of marketing mix on patient treatment decisions at the General Hospital of Rokan Hulu.Populasi in this study were all inpatients at hospitals Rokan Hulu.Untuk then taken to determine the amount of the assessed population characteristics. However, because the number of patients could not be determined who entered each day then to take the sample used insedentil sampling method that is based on taking samples that are considered characteristic spontaneity. The methods used in collecting data from each respondent using the techniques of inquiry / questionnaire. And subsequent data analysis using descriptive analysis techniques percentage. The results and discussion indicate that most elements of marketing mix elements play a role is the price at which the respondents chose the statement went to the hospital because of the low price.